Inflammatory Breast Carcinoma. A Case Report - Dianarelys Villafuerte Delgado; José Jamil Torres Aranda; Martha Yudey Rodríguez Pino (Revista Finlay, 2016)
Inflammatory breast carcinoma is a rare and aggressive type of breast cancer. It is distinguished from other breast carcinomas due to its clinical presentation, aggressiveness, and poor prognosis. We present the case of a female patient with a history of controlled hypertension. She sought medical attention because of redness in the right breast accompanied by partial retraction of the nipple. On physical examination, redness covering more than half of the breast, thickened skin, and palpable axillary lymph nodes were found. A mammogram revealed an asymmetric density in the right breast. She underwent a right axillary ultrasound that showed various lymphadenopathies. Conventional imaging methods remain valuable tools for the accurate diagnosis of inflammatory breast carcinoma.